Western Blotting: An Introduction - Kurien, Biji T. (Methods Mol Biol, 2015)
Western blotting is an important procedure for the immunodetection of proteins, particularly proteins that are of low abundance. This process involves the transfer of protein patterns from gel to microporous membrane. Electrophoretic as well as non-electrophoretic transfer of proteins to membranes was first described in 1979. Protein blotting has evolved greatly since the inception of this protocol, allowing protein transfer to be accomplished in a variety of ways.